The relationship between work stress and well-being among Chinese primary and secondary school teachers: The chain mediation of affective rumination and work engagement - Yanhong Shao; Wenxuan Jiang; Hongdong Zhu; Chao Zhang; Weili Xu (BMC Psychology)
Abstract Background Although scholars have explored the impact of work stress, affective rumination, and work engagement on teachers’ well-being, there is a need for more research to investigate the mechanisms through which work stress influences teachers’ well-being via affective rumination and work engagement. Methods Based on the Conservation of Resources Theory and the Job Demands-Resources Model, this study examined the potential indirect roles of affective rumination and work engagement in the association between work stress and well-being among primary and secondary school teachers. A paper questionnaire survey was administered to 760 primary and secondary school teachers (M = 39.84, SD = 8.848) selected through cluster sampling from nine schools in Yancheng City, Jiangsu Province, China. All participants completed structured self-report questionnaires, including measures of work stress, affective rumination, work engagement, and well-being. Data analyses were conducted using structural equation modeling via Amos 24.0. Results The results are as follows: (1) Work stress has a direct and negative effect on well-being; (2) Work stress indirectly and negatively affects well-being through affective rumination; (3) Work stress indirectly and negatively affects well-being through work engagement; (4) Work stress indirectly and negatively impacts well-being through both affective rumination and work engagement. Conclusion The results underscore the detrimental effects of work stress and identify the feasibility of interventions targeting affective rumination and work engagement, offering insights into strategies to promote the well-being of primary and secondary school teachers.